Relationship between posterior dentoalveolar vertical dimension and skeletal classification in orthodontic patients treated with and without first premolar extractions: a cephalometric analysis - González-Sauter, María Piedad; Grajales-Ramírez, Marggie; Tanaka-Lozano, Eliana Midori (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: the purpose of this study was to determine and to cephalometrically compare the variation of posterior dentoalveolar vertical dimension in orthodontic patients treated with and without extraction of first premolars in Class I and Class II malocclusions and to establish its correlation by means of the Anteroposterior Dysplasia Indicator (APDI). Mehods: pre (T1) and post (T2) treatment lateral cephalograms of 76 patients from Fundación CIEO, aged 22 to 45 years, were skeletally classified according to APDI and the type of treatment received, regardless of gender, forming four groups: Class I with and without extractions, and Class II with and without extractions. The posterior dentoalveolar vertical dimension was calculated with linear measurements and its variation among the malocclusion groups was statistically analyzed; also, a multiple correlation analysis between dentoalveolar heights and APDI was performed at T1 and T2. Results: the intragroup analysis showed a significant increase of posterior dentoalveolar vertical dimension at T1 and T2 in both Class I and Class II groups with first premolar extractions at the lower second premolar (5i) and upper second molar (7s), respectively. The intergroup analysis showed a significant increase in posterior dentoalveolar vertical dimension, according to skeletal malocclusion class, in treatments with first premolar extractions, at the upper second premolar (5s), upper first molar (6s), upper second molar (7s), and lower first molar (6i). Conclusions: there was an increase of posterior dentoalveolar vertical dimension at T1 and T2 in all the groups, being statistically significant in Class I and Class II patients treated with first premolar extractions without altering the skeletal classification (APDI).